PPTTG Pencetak Pelet Untuk Peternak Ikan Koi Dusun I Timur Karang Anyar - Sitorus, Melvin; Pangaribuan, Lisda Juliana; Salman, Aulia; Benar, Benar (JUBDIMAS ( Jurnal Pengabdian Masyarakat), 2022)
Karang Anyar Village with an area of ​​4.63 km2 and a population of 9,366 apart from farming, the residents are also cultivating ornamental fish species of koi fish in ponds/ponds which are formed side by side with rice fields by utilizing good irrigation around the pond, including Mr. Hendrayen as this service partner currently has land for a fish pond of 2.4 hectares with fish pellets as the main feed which currently relies heavily on factory-made fish feed, the price of which is not affordable by most farmers in Karang Anyar Village with the need for pellets. per day for 36 kg, for that the service implementation team carried out activities in the form of demonstrations on the use of pellet molding machines, training on the use of pellet molding machines and their maintenance as well as machine handover which during demonstrations, the machine was able to produce 50 kg of pellets every hour with cylindrical pellets of diameter 3 mm long and 4 mm long